2021
DOI: 10.3390/cli9110165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Climate Change on Streamflow, Sediment, and Nutrient Load at Watershed Scale

Abstract: This study evaluated changes in climatic variable impacts on hydrology and water quality in Big Sunflower River Watershed (BSRW), Mississippi. Site-specific future time-series precipitation, temperature, and solar radiation data were generated using a stochastic weather generator LARS-WG model. For the generation of climate scenarios, Representative Concentration Pathways (RCPs), 4.5 and 8.5 of Global Circulation Models (GCMs): Hadley Center Global Environmental Model (HadGEM) and EC-EARTH, for three (2021–204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…However, similar studies reported comparable increases in the catchment scale (TN up to 34%, TP up to 50% (Čerkasova et al, 2019). Local predictions are also high, but this has also appeared in the literature (Li et al, 2018;Parajuli & Risal, 2021;Schürz et al, 2019).…”
Section: Water Resources Researchsupporting
confidence: 54%
“…However, similar studies reported comparable increases in the catchment scale (TN up to 34%, TP up to 50% (Čerkasova et al, 2019). Local predictions are also high, but this has also appeared in the literature (Li et al, 2018;Parajuli & Risal, 2021;Schürz et al, 2019).…”
Section: Water Resources Researchsupporting
confidence: 54%
“…In addition to the anthropogenic causes, natural variables such as climate change have also had an impact on the streamflow variability [13][14][15][16]. Climate change has far-reaching ramifications in a way that it modifies precipitation timing, magnitude, and distribution, as well as evapotranspiration rates and general hydrological patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is a matter of concern for hydrologists, climatologists, environmentalists, and agronomists as it is anticiapted to have and increasingly serious impact on water resources, infrastructure, agriculture, biodiversity and ecosystem functioning, and human health [5][6][7][8][9]. Although climate change is experienced globall, the degree of its impact varies considerably from region to region [10,11].…”
Section: Introductionmentioning
confidence: 99%